Security Enhancing based on Node Authentication and Trusted Routing in Mobile Ad Hoc Network (MANET) - M. Venkat Das, P Premchand, L R Raju (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In theMobile Ad HocNetwork, identifying trusted nodes for secure communication is a key challenge. Node compromises a service and leads to ambiguity in the behaviour of a node in the network. Node authentication and trust level calculation will enhance the security aspect of MANETs. Thispaper proposes enhancing security based onthe "Node Authentication and Trusted Routingapproach (NATR)". NATR aims to avoid abnormal node interference in MANET. There through improved security and output data delivery. NATR calculates the predictability of the node by evaluating the three most common actions performed by a node in the connection process. Node licensing is a key aspect of evaluating custom network security. In this method, we monitor the Success rate of RREQ, Success rate of RREP, and Data Success rate node trust. The reliability of data delivery is measured bythe successfuldelivery of packets and theloss or drop of packets. The experimental results showthere is a 25% increase in package delivery and a 40% decrease in overhead for routing. NATR is compared with SAR TMS, and AODV to assess efficiency in Adhoc networks